The historical development and the results achieved for Iraq in the performance of high jump efficiency in the Arab sessions for the period from 1953 to 1976 - م.م. نضال هاشم غافل أ.م.د زينب علي عبد الامير أ.م.د اسيل جليل كاطع (physical education and sport sciences college for women/ Baghdad University, 2018)
Historical development and results achieved for Iraq in the performance of effectiveness Arabic courses for the high jump from 1953 until 1976 m research analytical historical Nedhal Hashem inattentive abstract: this research consisted of five sections: the first section presented and the importance of research and research issue which included document Iraq shares in Arabic courses in 1953 m until 1976 in effectively performing high jump and find out the real reasons and documented in case of non-participation of Iraq to some of these courses. The researcher trying to have this research serves as an effective contribution to the newborn modest in construction project of scientific research in our beloved country. And also ensure that the door on research objectives-identify the historical development of the performance effectiveness of the high jump. -To identify achieved results for Iraq in Arabic courses for the period 1953 m until 1976 to perform effective high jump. -Analyze the participation of Iraq to Arabic courses for the period and the results achieved. -Explain the reasons for non-participation of Iraq to any of these courses. Also included in this section on areas of research: temporal area: the researcher search procedures for the period of Until 15 March 2018.  -Spatial domain: library faculty of physical education and sports science and physical education College Library, the Jadiyera library of the Iraqi Olympic Committee.  -Human domain: players participating in Arabic courses from 1953 until 1976. Methodology of research: research adopted experimental method to study.  Section II: theoretical studies: this section stages of historical development to perform effective high jump.  Section III: this chapter contains offer to Iraq shares in Arabic courses since 1953 and Syria until 1976. And results achieved. Section IV: outline and analysis of Iraq shares this courses with a discussion of the reasons for non-participation of some such courses as statistical variables of digital progress as well as the historical curve for the logarithm of height, progress and decline in level.